High-temperature quantum oscillations caused by recurring Bloch states in graphene superlattices - Krishna Kumar, R.; Chen, X.; Auton, G.H.; Mishchenko, A.; Bandurin, Denis A.; Morozov, S.V.; Cao, Y.; Khestanova, E.; Ben Shalom, M.; Kretinin, A.V.; Novoselov, K.S.; Eaves, Laurence; et al. (American Association for the Advancement of Science, 2017)
Cyclotron motion of charge carriers in metals and semiconductors leads to Landau quantization and magneto-oscillatory behavior in their properties. Cryogenic temperatures are usually required to observe these oscillations. We show that graphene superlattices support a different type of quantum oscillations that do not rely on Landau quantization. The oscillations are extremely robust and persist well above room temperature in magnetic fields of only a few T. We attribute this phenomenon to repetitive changes in the electronic structure of superlattices such that charge carriers experience effectively no magnetic field at simple fractions of the flux quantum per superlattice unit cell. Our work points at unexplored physics in Hofstadter butterfly systems at high temperatures.